Sexual-i-hablando, las representaciones sociales de las estudiantes de Educación Preescolar en relación con la Educación para la Sexualidad - Sánchez López, Martha (2008)
Due to the current need for information and mainly formation towards the topic about sexuality, it becomes a necessity to learn about the representations that Preschool Education students have around the class taught by the DEB (Division de Educacion Basica); specifically it deals with contents, methodologies and strategies that will for sure influence placing into practice the knowledge acquired in the classroom. The present investigation aboards the representations that Preschool Education students from the DEB (Division de Educacion Basica) have about the class «Sexual Education» that is taught in the IV bachelor level; departing from the previous information about sexuality that these students have and the expectations related to their field work (student practice in preschool classrooms) about sexual education. All of the previous information has the purpose to reflect about the impact in the pedagogical and subjective level that the methodological proposal and the contents themselves show. The methodology used, from a qualitative point of view, considered adequate making profound interviews as well as taking into account stories that illustrate experiences for situations lived around sexual education for students sexuality, also the doubts and fears during their field work and the strategies to come over this issue, among others. The investigation obtained as a result a proposal in content and method for this class. Also, it suggests educational strategies in the classroom coming from the professors in charge, and as a consequence the incorporation of these strategies by the students during their field work. Besides, a test with incomplete sentences (TOI), designed to know the general information that students who will take this class handle, related to sexuality, sexual education, women sexuality, women, adolescents and girls, as well as men sexuality, adolescents and children.